الحيل وعلاقتها بالتعسف في استعمال الحق - الغول, محمد; القضاة, علاء (University of Eloued جامعة الوادي, 2019)
تهدف هذه الدراسة التعرف على أحكام الحيل، وعلاقتها بالتعسف في استعمال الحق في "دعاوى النفقات في قانون الأحوال الشخصية الأردني " نموذجاً. وتكمن مشكلة الدراسة في بيان مدى الصلة بين الحيل والتعسف في استعمال الحق في الفقه الإسلامي. وتتمثل أهمية الدراسة في عدم وجود دراسة مستقلة توضح علاقة الحيل والتعسف في استعمال الحق في الفقه الإسلامي. وقد اعتمد الباحثان في هذه الدراسة على المنهج الاستقرائي والمنهج التحليلي: وذلك بتتبع الأحكام المتعلقة بموضوع الدراسة من مظانها من القرآن الكريم، السنة المطهرة، والكتب الفقهية، ومحاولة فهم النصوص، ودراستها بشكل علمي. وقد توصل الباحثان إلى جملة من النتائج كان من أبرزها: أن قاعدة الحيل تمثل المعيار الذاتي للتعسف، وأن صاحب الحق إذا استعمل حقه وقصد به تحقيق مصلحة ولكن حدث ضرر بالغير فإنه يعد متعسفا. Abstract Prepared by Dr. Alaa Ahmad Al- qodah Dr. Mohammed Ahmad Al- Ghou This study aims to identify ahkamalhiyal(the provisions of tricks) and their relationship to the abuse of using the right in “the legal claims for maintenance in the Personal Status Law” as a model. The problem of the study lies in explaining the relationship between tricks and the abuse of using the right in the Islamic jurisprudence. The importance of the study is derived from the absence of an independent study that illustrates the relationship between alhiyal(the tricks) and abuse of using the rights in the Islamic jurisprudence. In this study، The researchers relied on the inductive and analytical methods by tracing the provisions related to the subject of the study from its sources، namely the Holy Quran، the Sunna of the Prophet، the books of Islamic law، and trying to understandand study the texts in a scientific manner. The researchers has obtained a number of results، most notably: The rule of tricks constitutes the subjective criterion of right abuse. It was also found that if the eligible party uses his right with the intention to achieve interest but damageoccurs to others، he/she shall be considered absolutist. Keywords :Tricks , abuse, right, claims for maintenance, Personal Status Law
دعاوى النفقات في قانون الأحوال الشخصية الأردني " نموذجا
مقال بمجلة الشهاب
Keywords: الحيل ، التعسف ، الحق ، دعاوى النفقات ، الأحوال الشخصية